ANALISIS TINGKAT KERUSAKAN PANTAI AKIBAT BENCANA ABRASI DAN UPAYA PENANGANANNYA (PESISIR DESA STOWE BRANG) - Handika Minarno; Adi Mawardin (Program Studi Teknik Sipil, Fakultas Teknik Universitas Teknologi Sumbawa, 2024)
Abrasion that occurs in Sumbawa Regency, Utan District, Stowe Brang Village is caused by wave factors, land characteristics which are generally in the form of peat, silt and sand are very vulnerable to erosion due to waves. In addition to natural factors, abrasion can also be blamed on human factors. The variables used in this study consist of 2 of them, namely: (1) Natural Factors, (2) Human Factors. The purpose of this study is to describe the coastal condition of Stowe Brang Village, Utan District, Sumbawa Regency. The analysis method used is Descriptive Analysis with a combination of Quantitative and Qualitative. To assess the condition of damage to coastal areas, it is necessary to survey the location of mangrove vegetation conditions, how far the coastline is to the pond, and the condition of the river estuary at the site. Furthermore, based on the value of the coastal damage index, the prioritization of handling refers to SE PU No. 11 of 2021. Based on the results of the analysis, there are several factors that affect the occurrence of abrasion at the study site, including factors still lack of vegetation on the beach, flat land slope factors, sandy beach type factors and the absence of coral reefs, sea wave factors that are large enough. To get wave plan data requires wind data for 10 years, tidal data, topographic data and bathymetry. Based on the results of data analysis, the wave height of the 10-year plan with the Gumbel method is 0.4 m. The form of handling efforts that can be done is the addition of mangrove vegetation and can also be done by building coastal protection constructions such as breakwater construction with plain concrete blocks